Validação do ensaio genético de identificação de espécies de pescado por DNA Barcode segundo ABNT NBR ISO/IEC 17025 e desenvolvimento de método para identificação molecular de espécies de salmão e trutas por minissequenciamento - Danilo Alves Pimenta Neto (2017)
The present study describes the optimization and standardization of the method of identification of fish species by DNA Barcode as well as its validation according to the requirements of ABNT NBR ISO / IEC 1705 for accreditation with INMETRO and later accreditation with the MAPA with the objective of providing the identification service, which can help entrepreneurs choose their suppliers and quality control of their products, as well as consumers to have greater confidence in what they are consuming. It can also assist the government in testing products to prevent fraud, as well as regulate products exported and imported more effectively. It also proposes a new method for molecular identification of trout and salmon at the level of genus and / or species. This method is based on amplification followed by minissequencing of part of the D-loop region of the mitochondrial DNA of the fish. By means of this method, it is possible to identify the two genera and the four most prevalent salmon and trout species, Salmo salar, Oncorhynchus keta, O. gorbuscha and O. mykiss.